Causation between Agronomic Traits in Homozygous Soybean Lines - ADIE , Mochammad Muchlish; KRISNAWATI, Ayda (Walailak Journal of Science and Technology (WJST), 2021)
Seed yield in soybean is associated with other yield components. The objective of the study was to investigate the pattern of relationship between seed yield and yield components in soybean. Agronomic characters and seed yield of 147 soybean homozygous lines (HL) and 3 check cultivars (Dega 1, Detap 1, and Anjasmoro) were evaluated in Banyuwangi (East Java, Indonesia) from April to July 2018. The field experiment was conducted in a randomized complete block design with 2 replications. After threshing, the HLs were grouped into large seed size (> 14.00 g/100 seeds) and medium seed size (10 - 14 g/100 seeds). The causation and inter-relationship between yield components and seed yield were quantified using path analysis. Based on the seed size, a total of 150 HLs was grouped into 97 lines and 53 lines of large and medium seed size, respectively. The correlation analysis showed a similar pattern between groups of large and medium seed size. The seed yield in both groups was highly determined by the characters of the number of filled pods, number of nodes, number of branches, plant height, and wet biomass. The results of path analysis revealed that plant age, particularly the length of the generative phase, was an important factor affecting seed yield in large seed soybean lines. The length of the generative phase determining the soybean yield in this study can be suggested to be used as selection criteria to obtain high yielding and large seed size variety. HIGHLIGHTS The investigation on the pattern of relationship between seed yield and yield components in soybean The path analysis to quantify the causation and inter-relationship between yield components and seed yield The soybean seed yield was highly determined by the characters of the number of filled pods, number of nodes, number of branches, plant height, and wet biomass The length of the generative phase could be used as selection criteria to obtain high yielding and large seed size soybean variety